2000
DOI: 10.1007/s002770050569
|View full text |Cite
|
Sign up to set email alerts
|

A phase-II trial of all trans retinoic acid and low-dose cytosine arabinoside for the treatment of high-risk myelodysplastic syndromes

Abstract: Twenty-two patients with high-risk myelodysplastic syndrome (HRMDS) were treated with a 10-day course of oral all trans retinoic acid (45 mg/m2) and s.c. low-dose cytosine arabinoside (LDARAc) given at the dose of 20 mg twice per day. The courses were repeated monthly until response or progression, in the case of response, the therapy was administered until relapse. Morphologic diagnoses were refractory anemia with excess blasts (RAEB) in nine, RAEB in transformation (RAEB-t) in nine, and chronic myelomonocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…78 When ATRA was used in conjunction with low-dose Ara-C in the treatment of "poor prognosis" AML, 48% (16/33) of the patients entered CR, and the CR rate was 88% in 17 patients with < 50% blasts in bone marrow. 79 It is noteworthy that a cytotoxic adverse effect cannot be excluded when low-dose chemotherapeutic drugs are used as differentiation-inducing agents.…”
Section: Treatment Of Apl With Arsenic Compoundsmentioning
confidence: 99%
“…78 When ATRA was used in conjunction with low-dose Ara-C in the treatment of "poor prognosis" AML, 48% (16/33) of the patients entered CR, and the CR rate was 88% in 17 patients with < 50% blasts in bone marrow. 79 It is noteworthy that a cytotoxic adverse effect cannot be excluded when low-dose chemotherapeutic drugs are used as differentiation-inducing agents.…”
Section: Treatment Of Apl With Arsenic Compoundsmentioning
confidence: 99%
“…[7][8][9] The clinical results of ATRA in non-APL AML have been variable. Venditti et al found that the combination of low-dose Ara-C and ATRA resulted in a remarkably high complete remission (CR) rate in a poor-prognosis AML patient population, particularly those with a lower marrow blast count, 10 but in a randomized phase 2 trial Estey et al found no benefit from the addition of ATRA to a fludarabine and cytarabine regimen in newly diagnosed poor prognosis AML and myelodysplastic syndrome. 11 Similarly, in a United Kingdom Medical Research Council (MRC) trial, we failed to demonstrate an overall advantage of adding ATRA to standard chemotherapy in patients who were deemed to have high risk AML or who had relapsed, 12 or to low-dose cytarabine or hydroxycarbamide as first-line treatment of older patients not considered fit for intensive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…44,47,48 We were unable to show a relationship between bcl-2 expression and the degree of protection from apoptosis in our previous study, and furthermore Del Bino et al demonstrated that DMSO-induced reductions in apoptosis preceded changes in bcl-2 expression, which only occurred after 72 h incubation with DMSO. 16,17 Previous studies which have examined the effect of diffentiating agents on apoptosis have shown the crucial importance of the relative timings of the two treatment modalities: preincubation of AML cells with ATRA, 1,25(OH) 2 D3 or DMSO is associated with cytoprotection on exposure to chemotherapy, whilst treatment with these differentiating agents after chemotherapy potentiates drug-induced DNA damage and cell death.…”
Section: Discussionmentioning
confidence: 74%
“…43 The current United Kingdom Medical Research Council AML trials, AML-12 and AML-14, include randomisations for the treatment of non-M3 AML cases with ATRA. [44][45][46] The cited rationale for the use of ATRA in such patients includes the down-regulation of bcl-2 by differentiation with retinoic acid, thus removing a powerful anti-apoptotic influence.…”
Section: Discussionmentioning
confidence: 99%